2012
DOI: 10.3109/08880018.2012.708891
|View full text |Cite
|
Sign up to set email alerts
|

T2* MRI in Regularly Transfused Children with Thalassemia Intermedia: Serum Ferritin Does Not Reflect Liver Iron Stores

Abstract: Nontransfused patients with thalassemia intermedia (TI) accumulate iron due to increased gastrointestinal absorption of iron. Recent studies using T2* MRI revealed that serum ferritin does not reflect the severity of iron overload in nontransfused TI patients. We evaluated the iron overload status in TI children on monthly transfusion. Based on serum ferritin levels, 11 such patients (mean age 13.18 ± 4.09 years), were classified into two groups, group 1 (six patients) and group 2 (five patients) with serum fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…After being on chronic transfusion therapy for four months, his growth improved to the 25 th centile, and his liver and spleen are palpable just under the costophrenic angle. The modest elevation in ferritin level, which is discrepant with the T2* of his liver showing moderate iron overload, is similar to what has been reported in patients with thalassemia intermedia [18]. Also, iron loading in thalassemia intermedia can occur even in the absence of prolonged transfusion therapy and responds well to iron chelation therapy [19].…”
Section: Resultssupporting
confidence: 68%
“…After being on chronic transfusion therapy for four months, his growth improved to the 25 th centile, and his liver and spleen are palpable just under the costophrenic angle. The modest elevation in ferritin level, which is discrepant with the T2* of his liver showing moderate iron overload, is similar to what has been reported in patients with thalassemia intermedia [18]. Also, iron loading in thalassemia intermedia can occur even in the absence of prolonged transfusion therapy and responds well to iron chelation therapy [19].…”
Section: Resultssupporting
confidence: 68%
“…It has been observed that serum ferritin levels can underestimate iron load in patients with β‐TI, compared with patients with thalassaemia major. Therefore, relying on this measurement may expose patients with NTDT to high iron levels and delay necessary chelation therapy . Similar findings were reported in the THALASSA trial of deferasirox in patients with NTDT including HbE/β‐thalassaemia and α‐thalassaemia .…”
Section: Transfusion Considerationssupporting
confidence: 66%
“…ref. [149][150][151][152][153][154][155][156][157][158], also widely used for brain imaging (e.g. ref.…”
Section: Serum Ferritin Can Be a Marker Of Iron Stores But Is Also Anmentioning
confidence: 99%